1993
DOI: 10.1210/mend.7.8.8232318
|View full text |Cite
|
Sign up to set email alerts
|

The rat proenkephalin germ line promoter contains multiple binding sites for spermatogenic cell nuclear proteins.

Abstract: Rat and mouse spermatogenic cells contain a family of 1700-nucleotide (nt) proenkephalin mRNAs that are generated from an alternate, germ cell-specific promoter. This promoter is located approximately 350 base pairs (bp) downstream of the promoter used in somatic cells, within the first intron for the somatic transcript. In a previous study, rat proenkephalin-chloramphenicol acetyltransferase fusion genes containing both promoters were shown to be transcribed selectively from the germ cell promoter and in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Previous studies suggested that Gli-related proteins were present in rodent testes and spermatogenic cells (Galcheva-Gargova et al, 1993). To address this directly, Northern analysis was performed on puri®ed mouse cells representing varying stages of sperm maturation (Figure 1).…”
Section: Expression Of Gli Genes During Spermatogenesismentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies suggested that Gli-related proteins were present in rodent testes and spermatogenic cells (Galcheva-Gargova et al, 1993). To address this directly, Northern analysis was performed on puri®ed mouse cells representing varying stages of sperm maturation (Figure 1).…”
Section: Expression Of Gli Genes During Spermatogenesismentioning
confidence: 99%
“…Characterization of Gli DNA binding activities in testis and male germ cells Nuclear proteins were previously detected in spermatogenic cell extracts that formed cell-speci®c complexes with a region of the rat and mouse proenkephalin promoters containing a Gli consensus binding element in reverse orientation (Galcheva-Gargova et al, 1993). Gel shift studies were therefore performed to verify whether authentic Gli DNA binding activities were present in testis, and in particular, in spermatogonial cells.…”
Section: Polysome Analysis Of Gli Mrnas In Mouse Testismentioning
confidence: 99%
See 1 more Smart Citation
“…In order to explore transcriptional programs controlling spermatogenesis, we have previously examined the cell-and stage-specific regulation of the male germ line proenkephalin promoter in rodents (14,27). This promoter is expressed exclusively by spermatogenic cells and is highly up-regulated in pachytene spermatocytes and haploid round spermatids (55).…”
mentioning
confidence: 99%
“…These cells use an independent, alternate promoter within the single copy proenkephalin gene to synthesize a novel 1700-nt germ cellspecific mRNA (21). Previous studies have demonstrated that the rat proenkephalin germ line promoter is contained within a 500-bp TATA-less sequence located within the first somatic intron (22). While the upstream somatic promoter contains functional CRE elements (23), the germ line proenkephalin promoter lacks such consensus sequences.…”
mentioning
confidence: 99%